Edukasi Ketahanan Pangan Keluarga Oleh KKN 14 Batubulan Kangin di Banjar Buda Ireng - Nanda Jaya Pratama, I Gede; Ni Wayan Yuliantari; Putu Santi Oktarina; Luh Made Intan Pratiwi; Made Intan Kusumayanti; Luh Putri Juliantari; Rosesinta Thailandni Mahaputri; I Gusti Ayu Cintya Laksmi; Ni Komang Wien Hapsari Pradnyadevi; I Putu Nanda Saputra; I Gusti Ayu Leni Ulandari; I Made Agus Wira Putra; I Kadek Agastya Arta Putra; Ni Made Sri Gita Ayu Sukrayanti; Pande Putu Junita Utami (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Food security is a classic issue that always arises amid economic uncertainty and global instability. In this context, food security refers to the process of ensuring the sustainability of food supplies to prevent shortages. One of the issues contributing to food insecurity is the decline in agricultural and plantation productivity. This issue is also present in Batubulan Kangin Village, where agricultural and plantation land has decreased by 24%. In response to this issue, the Kelompok Mahasiswa KKN 14 Batubulan Kangin implemented the work program “Edukasi Berkebun di Rumah: Solusi Ketahanan Pangan Keluarga”The research method used in this study is descriptive qualitative, describing the implementation of the educational program activities for the community in Banjar Buda Ireng. The data collection techniques in this study include interviews with village officials, observations during the activities, and documentation of the implementation stages. The results of this study are the implementation of education with a preventive concept, in line with the SDGs program and the Balinese concept of life, Tri Hita Karana, with four stages of activity implementation, namely planning, organizing, leading, and controlling. The output of this activity is the distribution of chili and eggplant seeds to education participants as an incentive to implement the theories presented during the education program, thereby benefiting family food security